An Education on the Preparation of Face Mist Formulations for High School Students in Bekasi and South Tangerang: Indonesia - Ayuningtyas, Nurista; Cahaya, Gabriella; Feronia Reni Cyrena Santoso; Dela Rosa; Ernestine Arianditha Pranasti; Friska Dewi Sari Hutauruk (Jurnal Dimas, 2025)
Cosmetics have become a trend among young people; however, knowledge about their composition, safety, and production stages remains limited. Therefore, proper education on cosmetics is necessary, particularly regarding notification numbers, so that users can choose legal and safe products available in the market. Face mist is a cosmetic product in spray form that functions to increase the moisture of the facial skin. This community service aims to provide education on the formulation and application of face mist using cucumber extract as the main ingredient. Cucumber contains natural alpha hydroxy acids such as lactic acid, which helps reduce the thickness of the stratum corneum and is effective for various skin disorders. Additionally, the content of vitamin C and caffeic acid provides a soothing effect and reduces skin swelling. The activities were conducted through a pre-test, education by lecturers, face mist formulation practice, and a post-test. The results showed a progressive increase in participants’ average understanding from 85.75% to 95.63%, indicating that education combined with demonstration and hands-on practice by experts has a positive impact. This education and workshop enhanced students’ knowledge regarding safe and beneficial cosmetic products based on natural ingredients